Algorithm for Solving a New System of Generalized Nonlinear Quasi-Variational-Like Inclusions in Hilbert Spaces. (5th February 2014) - Husain, Shamshad; Gupta, Sanjeev; Sahper, Huma
Abstract : We introduce and study a new system of generalized nonlinear quasi-variational-like inclusions withH ( ·, · ) -cocoercive operator in Hilbert spaces. We suggest and analyze a class of iterative algorithms for solving the system of generalized nonlinear quasi-variational-like inclusions. An existence theorem of solutions for the system of generalized nonlinear quasi-variational-like inclusions is proved under suitable assumptions which show that the approximate solutions obtained by proposed algorithms converge to the exact solutions.